Black in blues how a color tells the story of my people - Perry, Imani 1972- (Harper Collins Pulishers, 2025)
"A surprising and beautiful meditation on the color blue - and its fascinating role in Black history and culture - from National Book Award winner Imani Perry. Throughout history, the concept of Blackness has been remarkably intertwined with another color: blue. In daily life, it is evoked in countless ways. Blue skies and blue water offer hope for that which lies beyond the current conditions. But blue is also the color of deep melancholy and heartache, echoing Louis Armstrong's question, "What did I do to be so Black and blue?" In this book, celebrated author Imani Perry uses the world's favorite color as a springboard for a riveting emotional, cultural, and spiritual journey--an examination of race and Blackness that transcends politics or ideology."-- Provided by publisher
Keywords: African Americans / Social life and customs; African Americans / History; African Americans / Race identity; Blue / Social aspects; Blues (Music) / Psychological aspects; HISTORY / African American & Black; SOCIAL SCIENCE / Black Studies (Global)